P165 Effects of interval exercise training on asthma symptoms and inflammation. (12th November 2019) - Freeman, AT; Hill, D; Gove, K; Cellura, D; Jack, S; Staples, KJ; Grocott, MPW; Wilkinson, TMA
Abstract : Introduction and objectives: Exercise intervention may modulate the inflammation responsible for asthma, offering clinical benefit beyond functional improvement. Interval training is tolerated in asthmatics, and may also improve symptom control. This proof of concept study has recruited sub optimally controlled, untrained asthmatics to a 12-week Interval Training Programme to ascertain feasibility and safety, and effect on symptom control, airway and systemic inflammation, and physical fitness. Methods: Participants completed thrice weekly 30-minute interval exercise training sessions for 12 weeks. The training intensities were prescribed based on oxygen uptake (VO2) at anaerobic threshold (AT) and peak exercise. Lung function, blood, exhaled breath, saliva, sputum and symptom questionnaires were sampled at baseline, 3, 6 and 12 weeks. Results: Early results (n=6) suggest safety and tolerability, with improvement in symptom scores using the Asthma Control Questionnaire score (Friedman p=0.003) and Asthma Quality of Life Questionnaire score (Friedman p=0.02). This improvement in symptoms was associated with reductions in peripheral blood total white cell count (Friedman p=0.02), neutrophil count (Friedman p=0.04), eosinophil count (Friedman p=0.0017), and lymphocyte count (Friedman p=0.04). There was a significant improvement in pre-bronchodilator FVC (Friedman p=0.04) but not FEV1, with a trend for reduction in percentage bronchodilator reversibility (Wilcoxon signed rank p=0.09). The training intervention did not significantly improve physical fitness, assessed by VO2 at anaerobic threshold (Friedman p=0.37) or peak (Friedman p=0.15). BMI did not significantly change (Friedman p=0.18) and exhaled nitric oxide (FeNO) did not significantly improve (Friedman p=0.5). Conclusions: This interim analysis suggests exercise intervention in sub optimally controlled asthma is tolerated and beneficial for symptom control, with associated improvement in inflammatory parameters and lung function. The stability of BMI suggests the improvements in inflammatory markers are not a result of reduced adipose tissue related systemic inflammation. The stability of FeNO and significant reductions in total white cell and neutrophil count suggest the improvement in symptoms and inflammation are not due to improved adherence to inhaled corticosteroids. Prescribed training programmes may provide a cost-effective, disease modifying treatment adjunct in poorly controlled asthma.